Moving out of Islam on YouTube: Acehnese Christian Narratives, the Public Sphere, and Counterpublics in Indonesia - Ansor, Muhammad (Studia Islamika, 2024)
This study examines the public sphere and the formation of counterpublics based on the narratives of former Muslims from Aceh who converted to Christianity on YouTube. This study argues that in addition to strengthening the distinct attributes of Islamic identity in the public sphere, YouTube enables Acehnese former Muslims, as a subaltern community, to negotiate new social identities and share religious experiences after conversion. It also explores how Acehnese former Muslims challenge the dominant culture and restrictive regulations in Aceh, which perceive religious conversions as heresy and unlawful conduct. Data were collected using the digital ethnographic technique from four of the YouTube narratives of twelve Acehnese former Muslims who had converted to Christianity. The findings indicate that the online public sphere enhances the autonomy and their capacity to negotiate their Acehnese social identity, which is closely constructed with Islam. The presence of YouTube content thus contributes to strengthening the development of democracy and freedom of religious practice in Indonesia.